Exchange Rate Regime in Russia, Evaluation and Recommendations - Olga, Vasilevskaya (2009)
This paper studies exchange rate choice in Russia with respect to social, economic and political determinants. The study deliberately narrowed the scope of the discussion to two extreme cases, i.e. fixed and floating exchange rate. Today Russia applies managed floating exchange rate arrangement and it is important to determine the direction of the further monetary policy development either towards fixed or floating exchange rate. The paper argues that the logical extension of the historical trend is a shift to an independently floating exchange rate arrangement.